Consolidación y complicaciones en el tratamiento de las fracturas de tibia distal tratadas con técnica mínimamente invasiva en el Hospital Regional Docente de Trujillo - Becerra Pérez, Julio César (2016)
Objective: Determine the time of consolidation in the distal tibia fractures and complications associated with the treatment of distal tibial fractures treated with minimally invasive technique at Regional Hospital of Trujillo. Materials and methods: An observational, prospective and descriptive study of 16 patients who underwent surgery for distal tibia fractures minimally invasive was performed by technical service of Surgery of Regional Teaching Hospital of Trujillo during the period between January 2013 and December 2013 are within the inclusion criteria. Results: Of 16 patients with distal tibial fracture treated with minimally invasive technique, 81.25% were men, the largest age group was between 35 and 45 years with a 56.25% and an average of 39 years. 93.75% of all fractures were categorized with AO International Classification in the category having the following distribution 43A, A1: 31.35% (5) // A2: 56.25% (9) // A3: 6.25% (1) and the rest (1) it was rated 43B1. The found mean follow-up was 15 months (range 12-21 months) and the average time of consolidation was 40 weeks (34-59 weeks). Malunion was a complication with the largest meeting of its kind in pain (100%), limitation of movement (87.5%) and deformity (43.8%) continue to material failure and 12.5% infections 6.3%. No nonunion and skin necrosis were observed. The need for reoperation was only observed in 2 patients (12.5%). Conclusion: The type of fracture was more presence according to the International Classification AO 43A2: 56.25% (9 patients) and C classification was not taken into account, the average follow-up time was 15 months, the time used in consolidation IMR is lower than that of other techniques for treating distal tibia fractures, with an average of 40 weeks. TMI generates the least amount of hassle unlike other techniques of distal tibia fractures, within which, malunion complication was the most presence, no nonunion and skin necrosis were observed, while the need for reoperation was only observed in 2 patients (12.5%).